Preoperative intravenous iron before cardiac surgery: a prospective multicentre feasibility study. (March 2020) - Klein, Andrew A.; Chau, Marisa; Yeates, James A.; Collier, Timothy; Evans, Caroline; Agarwal, Seema; Richards, Toby; ,
Abstract: Background: Preoperative anaemia affects one third of patients undergoing cardiac surgery and is associated with increased mortality and morbidity. Although it is recommended that perioperative teams should identify and treat patients with preoperative anaemia before surgery, introducing new treatment protocols can be challenging in surgical pathways. The aim of this study was to assess the feasibility and effectiveness of introducing a preoperative intravenous iron service as a national initiative in cardiac surgery. Methods: We performed a multicentre, stepped, observational study using the UK Association of Cardiothoracic Anaesthesia and Critical Care Research Network. The primary feasibility outcome was the ability to set up an anaemia and intravenous iron clinic at each site. The primary efficacy outcome was change in haemoglobin (Hb) concentration between intervention and operation. Secondary outcomes included blood transfusion and hospital stay. Patients with anaemia were compared with non-anaemic patients and with those who received intravenous iron as part of their routine treatment protocol. Results: Seven out of 11 NHS hospitals successfully set up iron clinics over 2 yr, and 228 patients were recruited into this study. Patients with anaemia who received intravenous iron were at higher surgical risk, were more likely to have a known previous history of iron deficiency or anaemia, had a higher rate of chronic kidney disease, and were slightly more anaemic than the non-treated group. Intravenous iron was administered a median (inter-quartile range, IQR [range]) of 33 (15–53 [4–303]) days before surgery. Preoperative intravenous iron increased [Hb] from baseline to pre-surgery; mean (95% confidence interval) change was +8.4 (5.0–11.8) g L −1 ( P <0.001). Overall, anaemic compared with non-anaemic patients were more likely to be transfused (49% [59/136] vs 27% (22/92), P =0.001) and stayed longer in hospital (median days [IQR], 9 [7–15] vs 8 [6–11]; P =0.014). The number of days alive and at home was lower in the anaemic group (median days [IQR], 20 [14–22] vs 21 [17–23]; P =0.033). Conclusion: The development of an intravenous iron pathway is feasible but appears limited to selected high-risk cardiac patients in routine NHS practise. Although intravenous iron increased [Hb], there is a need for an appropriately powered clinical trial to assess the clinical effect of intravenous iron on patient-centred outcomes.